Cover Feature: CO2 Hydrogenation with Cu/ZnO/Al2O3: A Benchmark Study (ChemCatChem 12/2020). Issue 12 (2nd June 2020) - Ruland, Holger; Song, Huiqing; Laudenschleger, Daniel; Stürmer, Sascha; Schmidt, Stefan; He, Jiayue; Kähler, Kevin; Muhler, Martin; Schlögl, Robert
Abstract : The Cover Feature shows the concept of CO2 hydrogenation as a chemical battery in the scope of a chemical energy conversion. It can be used to store renewable energy by synthesizing methanol from H2 obtained from renewable energy sources and CO2 from industrial waste gases. In their Full Paper, H. Ruland et al. demonstrate the extraordinary stability and high performance of an industrial Cu/ZnO/Al2 O3 catalyst for methanol production from feed gases with high CO2 concentrations. Especially, the catalytic system can work with a similar stability even under dynamic reaction conditions, which may be essential to integrate renewables into the process. More information can be found in the Full Paper by H. Ruland et al.